The Consumption of Antithrombin III During Coagulation, Its Consequences for the Calculation of Prothrombinase Activity and the Standardisation of Heparin Activity - Béguin, S; Kessels, H; Dol, F; Hemker, H C (Thrombosis and Haemostasis, 1992)
The decay rate of thrombin in plasma is shown to be linearly proportional to the concentration of antithrombin III (AT III), not only in the absence but also in the presence of heparin. This is a consequence of partitioning of heparin between AT III and other plasma proteins.In previous articles we calculated the prothrombin converting activity assuming a fixed concentration of AT III. Since AT III is consumed during the clotting process, prothrombinase activity is more accurately approximated using an algorithm that counts with the decrease of the AT III concentration. It is shown this leads to higher prothrombinase activities. The (absence of) inhibition of prothrombin conversion by prothrombinase in the presence of heparins found with the previous method is also found using the new algorithm.From the results presented it is evident that characteristic parameters of heparin action have to be normalised to the AT III concentration. On this basis we define a Standard Independent Unit of the antithrombin activity of heparin.